Fat Is Consistently Present within the Plantar Muscular Space of the Human Foot—An Anatomical Study - Joanna Tomlinson; Stefan Klima; Amélie Poilliot; Johann Zwirner; Niels Hammer (Medicina, 2022)
Background and Objectives: The foot comprises of active contractile and passive connective tissue components, which help maintain stability and facilitate movement during gait. The role of age- or pathology-related degeneration and the presence of fat within muscles in foot function and pain remains unclear. The existence of fat has to date not been quantified or compared between individuals according to age, sex, side or subregion. Materials and Methods: 18 cadaveric feet (mean age 79 years) were sectioned sagittally and photographed bilaterally. Fat in the plantar muscular space of the foot (PMSF) was quantified through the previously validated manual fat quantification method, which involved observing photographs of each section and identifying regions using OsiriX. Fat volume and percentage was calculated using a modified Cavalieri’s method. Results: All feet had fat located within the PMSF, averaging 25.8% (range, 16.5–39.4%) of the total PMSF volume. The presence of fat was further confirmed with plastination and confocal microscopy. Conclusions: These findings suggest that fat within the PMSF is a consistent but highly variable finding in elderly cohorts. Fat within the foot muscles may need to be considered a norm when comparing healthy and non-healthy subjects, and for therapeutic interventions to the foot. Further work is required to understand in detail the morphological and mechanical presence of fat in the foot, and compare these findings with pathological cohorts, such as sarcopenia. Additionally, future work should investigate if fat may compensate for the degeneration of the intrinsic muscles of the foot, with implications for both the use of orthotics and pain management.